Maintenance Analysis Based on Reliability of Main Engine Lubrication System with Markov Method - Imam Pujo Mulyatno; Ocid Mursid; Hartono Yudo; Sri Nurhumairoh (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
Maintenance of the main engine lubrication system determines the engine’s performance and components based on the standard of Japan Institute of Plant Maintenance. The purpose of the system analysis is to determine the critical components and evaluate every lubrication system component as a base on maintenance planning as a preventive measure to avoid downtime during ship operations. Data needed are the ship’s motion, damage frequency, components’ downtime, and lubrication system diagram. Data was analyzed qualitatively with Failure Mode and Effect Analysis and Fault Tree Analysis as well as quantitatively with Overall Equipment Effectiveness, Markovian Decision Process, and damage distribution. Results show that LO filter crisis components with 120 RPN and LO Pump (standby) with 105 RPN. FTA analysis results there are 3 lost types cause happening failure system that is pressure oil low , overheating of the oil , and there is pollution in oil. At its steady-state conditions, have a probability of 0.45 to experience moderate damage and 0.55 to be severe damage. Therefore, it is recommended to carry out maintenance before passing the MTTF value of each component so that the system can work optimally.